Consumer Behavior in Choosing Madrasah ‎Education Institutions: Kotler’s Perspective - Baharun, Hasan; Ulfa Diana (State Islamic Institute of Madura, 2023)
The purpose of this study is to investigate the community's choice-making behavior using Kotler's four-pillar model: product, price, place, and promotion. This study uses a qualitative approach with a case study. In-depth interviews with key informants, along with careful observation and recording gained during the field study, were the primary methods for data collection. The method of data analysis was carried out cyclically, with the stages of data display, data reduction, and conclusion serving as the checkpoints. According to the research findings, cunsomer behavior in choosing madrasa education institutions is influenced by marketing stimuli/mix, in addition to other stimuli and buyer responses. The findings of this research have ramifications for the necessity of management of educational institutions knowing the desires and requirements of the community for the path of institutional development.